2022
DOI: 10.3390/pharmaceutics14102178
|View full text |Cite
|
Sign up to set email alerts
|

Chromogranin A and Its Fragments in the Critically Ill: An Expanding Domain of Interest for Better Care

Abstract: Life-threatening diseases challenge immunity with a release of chromogranins. This report focuses on Chromogranin A (CGA) and some of its derived peptides in critically ill patients, with attention paid to their potential to become biomarkers of severity and actors of defense. First, we studied whether circulating CGA may be a biomarker of outcome in non-selected critically ill patients: CGA concentrations were reliably associated with short-term death, systemic inflammation, and multiple organ failure. Additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Also, for trauma patients, CgA levels can predict the onset of nosocomial infections, and their CgA-derived peptides can act as inhibitors of inflammation and antimicrobial peptides. Finally, they also demonstrated that a 4% concentration of non-oxidized albumin infusion reverses the multimerization of these peptides, restoring their anti-inflammatory and antimicrobial properties [4]. They concluded that CgA and its peptides could be considered relevant biomarkers in critically ill patients.…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…Also, for trauma patients, CgA levels can predict the onset of nosocomial infections, and their CgA-derived peptides can act as inhibitors of inflammation and antimicrobial peptides. Finally, they also demonstrated that a 4% concentration of non-oxidized albumin infusion reverses the multimerization of these peptides, restoring their anti-inflammatory and antimicrobial properties [4]. They concluded that CgA and its peptides could be considered relevant biomarkers in critically ill patients.…”
mentioning
confidence: 95%
“…One of the significant aspects of Dr. Metz-Boutigue's remarkable success has been her collaborative spirit, as she has fostered partnerships with brilliant researchers worldwide. Among her notable collaborators are Prof. Schneider, renowned for his expertise in intensive care medicine and infection, and together they discovered the role of several AMPs as biomarkers in critically ill patients [4]; Dr. Prévost, an expert in microbiology, who, together with Dr. Metz-Boutigue, identified new AMPs against resistant S. aureus strains [5]; and Dr. Goumon, an expert in neuroscience, with whom Dr. Metz-Boutigue discovered several AMPs derived from the neuroendocrine system [6]. Of note are her collaborations with Dr.…”
mentioning
confidence: 99%
See 1 more Smart Citation